Good publication practice in physiology 2021 - Boye L. Jensen; Pontus B. Persson (2021)
Acta Physiologica is committed to upholding the highest possible standards in the quality of reporting of biomedical research data. Thus, Guidelines for Good Publishing Practice in Physiology are published and updated biennially, to aid and guide authors, editors and reviewers alike in maintaining these standards.1 As a society-owned journal, Acta Physiologica focuses on publishing high-quality original research.2 Although review articles, generally speaking, gather more citations, Acta Physiologica has recently seen an almost dramatic increase in citations, a fact that both reflects the high quality of the original articles published in Acta Physiologica and reinforces the journal's responsibility for adhering to the highest standards in data reporting.3 The following paragraphs will highlight current developments and revisions of guidelines relevant for everyone involved in the process of biomedical publishing. The current update of the International Committee of Medical Journal Editors (ICMJE) guidelines may seem minor at first glance4; however, it tackles at least two main points which, in addition to impacting the quality and integrity of biomedical publishing, directly affect the public perspective on the conduct and reporting of research done in the life sciences. Firstly, requirements for disclosure of financial and non-financial author activities and relationships and real as well as perceived conflicts of interest have been rephrased in a more exact way, avoiding ambiguity and strengthening author responsibility. Secondly, ICMJE aids authors in acknowledging diversity aspects, as is often required from public funding agencies and the public, and which, however, many authors and researchers have struggled with addressing appropriately in the past. Smaller but nevertheless highly important changes pertain, for example to not citing predatory or pseudo-journals, to clinical trial registration and to acknowledge the contributions of junior academic staff supporting reviewers. As numerous research questions in Physiology keep requiring the use of research animals, expectations of the public, major funding bodies and legislation keep increasing. Studies planned and executed in accordance with the current 3R recommendations and then reported in agreement with the ARRIVE guidelines, ensure the highest possible standards in the design and conduct of animal research, to both comply with ethical requirements and obtain high-quality conclusive results. The current major update of the ARRIVE Guidelines for reporting animal research5 aims at both structural and content-related improvements, since secondary research showed, in spite of the endorsement of the ARRIVE guidelines by the majority of high-quality biomedical journals, that critical information required by the guidelines was still missing from the vast majority of publications sampled, and that editorial intervention largely failed to improve that situation (see, eg the ICARus Trial that tested the effect of requesting full ARRIVE compliance in the manuscript submission process6). In addition to improvements made to the clarity of the content, ARRIVE 2.0 includes the so-called "Essential 10" to describe the basic minimum requirements in manuscripts reporting animal experiments. A "Recommended Set," in addition, helps add context to the study, while a new "Explanation and Elaboration" document is intended to help authors better understand the context and rationale of the required items. Studies submitted to Acta Physiologica are expected to comply with the ARRIVE guidelines in their current version at the time of manuscript submission. Especially, the exact sample size must be described and power calculations including the assumptions made regarding the minimal relevant difference (effect size) and significance threshold. We encourage authors to apply the reporting guidelines from clinical studies, that is CONSORT when reporting on inclusion, dropouts, exclusion criteria and numbers that concluded the studies. In the format of a flow chart, this will in a simple way show key features of any series of animal experiments integrating numbers/groups, time and protocol (total number of animals, reasons for exclusion of animals and completion, sex of animals, source, species, strain, age, husbandry and strain characteristics of transgenic animals). The recommendations for the Replacement, Refinement and Reduction of Animals in Research (3R), first described by W. M. S. Russell and R. L. Burch in 1959, are intended to ensure that experimental research involving living non-human vertebrates and cephalopods is designed and conducted in a way that minimizes pain, suffering, distress and lasting harm. Both national and international legislation and regulations on the use of animals in research, as well as organisations that fund or conduct animal research, adhere to the 3R principles. This is especially true for national public funding agencies that support research which is of interest to the general public, and for whom, the publication record of applicants contributes significantly to their funding decisions.7 Moreover, given the high potential of controversy regarding animal research in public, especially when it is either tax-funded or conducted for-profit, it is noteworthy that opinion polls have consistently shown that public support for animal research has been conditional on the 3Rs being put into practice.8 Acta Physiologica is deeply committed to observing and promoting integrity in biomedical research reporting. As such, beautification of data is, in general, not acceptable. In addition to the tools, guidelines and instructions provided in the Author Guidelines, general principles of research integrity include common standards for the presentation of results and imaging data. A sample general overview of common principles of research integrity is provided in the European Code of Conduct for Research Integrity.9 Two practice examples are incorrect self-citations and the manipulative processing of digital imaging data, which are unfortunately relatively frequent issues in biomedical publishing. The Office of Research Integrity at the US Department of Health and Human Services provides a database of example cases and helpful tools for the detection of image manipulation.10 Acta Physiologica is currently revising its Author Guidelines with a special focus on, for example the accurate presentation of quantitative protein data with the use of antibodies and data with quantitation at the level of 2D tissue sections. Here, it is strongly encouraged to use appropriate methods to obtain absolute quantification of molecules in biological fluids or tissue homogenates such as ELISA and radioimmunoassys and not immunoblotting typically after polyacrylamide gel electrophoretic separation of proteins. Use immunoblotting preferentially to obtain qualitative information on molecule (protein) size (molecular weight) and modification, for example oligomerization, cleavage, ubiquitylation and phosphorylation. In general, use rigorous validation and reporting on antibodies for reproducibility as detailed in Br J Pharmacol (2018 Feb; 175(3): 407-411) Uncropped images of immunoblots should be shown and separate blots should never be merged or manipulated and independent molecular weight marker should always be indicated. Appropriate negative and positive controls should be included. In physiological studies, organ morphology is often analyzed in 2D sections of tissue of interest by application of immunological methods to show the localization of a molecule. "Quantitative morphology" or "morphometry," which are poorly defined terms with no consensus, are next applied based on incorrect assumptions and insufficient reporting of the conditions (blinding, number of sections, representative sections from the whole organ). Here, the appropriate technique of stereology was developed decades ago (see Gundersen, HJG, J Microsc 1977;111:219) which allows "inferring on spatial structure from partial information, usually lower-dimensional data, which is usually in the form of sections of projections of the structure of interest" (Davy, P. and Miles, RE, J. Roy. Stat. Soc., 39: page 56) in an unbiased and quantitative way. This approach should be used to obtain quantitative data from tissue sections or projections on the number, length, surface and volume of the subject of interest. If not, data should be reported in a qualitative way. The International Committee on Publication Ethics (COPE) regularly updates its guidelines11 on publication ethics practices (eg ethical peer review and potentially necessary edits made to peer reviews, advice on how to handle the overlap of manuscript texts with an author's previously published work, cooperation of journals and institutions in research integrity cases or for managing the relationships of society-owned journals, societies and their publishers) which we recommend checking regularly for updates and new guidelines on controversial issues that regularly come up in biomedical publishing, and which Acta Physiologica acts in full compliance with. At Acta Physiologica, we believe that quality in science reporting is reflected in a journal's adherence to the highest standards in research integrity. Acta Physiologica concludes 2021 at an Impact Factor of currently 6.3, which does make our team proud. However, we also monitor the development of performance indicators other than the IF, which was never intended for competitive ranking of biomedical publications,12, aiming at avoiding favoured reporting of singular performance indicators.13 We wish to thank everyone who has contributed to making Acta Physiologica's achievements possible: Our readers, contributors, publishers and society members, for another outstanding year. The authors have declared no conflicts of interest.